Proyecto comercial para la exportación de chifles al mercado ecuatoriano en estados unidos - Castro Lozano, María Auxiliadora (2010)
The opportunity to supply a nostalgic market of Ecuadorian migrants in the United States, which retain their eating habits and look for ethnic products, being the “chifle” one of the most desired, is the main motivation for the development of the next Business Plan, the which consists in creating Plantain Foods Company, which shall be responsible for the export of "Verdecitos" to Ecuadorian migrants market in the United States, starting in the states of New York and New Jersey. To get a more accurate and detailed knowledge of the target market, it was produced a market research, which analyzed its size, characteristics and estimated market demand. Based on the required product volumes was performed the respective technical study for the selection of suppliers, in parallel with developing a marketing plan based on target market segmentation and competition. Within this plan were established differentiation strategies against the competition and marketing mix to market the product. Finally we proceeded with the preparation of Financial Study, which analyzed the most significant economic variables in this business to make a real projection of revenues, expenses and potential of it. The development of cash flow and financial statements, provided us with satisfactory indicator based on a minimum acceptable rate of return established by the shareholders.